2014
DOI: 10.1088/0029-5515/54/10/103003
|View full text |Cite
|
Sign up to set email alerts
|

Co-current rotation of the bulk ions due to the ion orbit loss at the edge of a tokamak plasma

Abstract: Flux-surface-averaged momentum loss and parallel rotation of the bulk ions at the edge of a tokamak plasma due to the ion orbit loss are calculated by computing the minimum loss energy of both the trapped and the passing thermal ions. The flux-surface-averaged parallel rotation of the bulk ions is in the co-current direction. The peak of the co-current rotation speed locates inside the last closed flux surface due to the orbit loss of the co-current thermal ions at the very edge of a tokamak plasma. The peakin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 33 publications
3
39
0
1
Order By: Relevance
“…Parallel momentum predicted by the present theory (dashed line), in comparison to the previous result (solid line)[14][15][16].…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Parallel momentum predicted by the present theory (dashed line), in comparison to the previous result (solid line)[14][15][16].…”
supporting
confidence: 56%
“…In a tokamak, a magnetic fusion torus in the shape of a donut, spontaneous toroidal spinup of core plasma is routinely observed after the Lowconfinement to High-confinement (L-H) transition [2][3][4][5][6][7][8]. To understand the physical mechanism of this so-called intrinsic flow, various theoretical models have been proposed: the effect of the residual Reynolds stress [9,10] on the momentum redistribution [11], the effect of turbulence intensity gradient [12] and the effect of thermal ion orbit loss [13][14][15][16] on the boundary flow, the effect of Coriolis force on the momentum pinch [17,18], and the turbulent acceleration [19,20]. However, it is still an open issue to predict the net core flow in ITER.…”
Section: Introductionmentioning
confidence: 99%
“…We note that inclusion of isotropization (due to scattering) in the calculation not only increases the intrinsic rotation by an order of magnitude but also broadens and weakens the rather distinctive peaking seen in the two calculations without scattering and in experiments. 12,[17][18][19] Our previous calculations and comparison with experiment of intrinsic rotation using the original calculation strategy No. 1 (subscript "orig" in Fig.…”
Section: Application To a Diii-d H-mode Shotmentioning
confidence: 99%
“…1-9). Stacey et al [10][11][12][13][14] have recently extended the Miyamoto 6 model for numerical calculations of the effects of these "ion orbit losses" (IOLs) on the interpretation of edge plasma transport, and deGrassie et al, 15,16 Stacey et al, 17,18 and Pan et al 19,20 have shown that the peaking of toroidal rotation in the plasma edge observed in experiment could be interpreted as intrinsic rotation due to ion orbit loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation